2011
DOI: 10.1371/journal.pone.0028963
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Stress at mHz Frequencies Aligns Fibroblasts in Direction of Zero Strain

Abstract: Recognition of external mechanical signals is vital for mammalian cells. Cyclic stretch, e.g. around blood vessels, is one such signal that induces cell reorientation from parallel to almost perpendicular to the direction of stretch. Here, we present quantitative analyses of both, cell and cytoskeletal reorientation of umbilical cord fibroblasts. Cyclic strain of preset amplitudes was applied at mHz frequencies. Elastomeric chambers were specifically designed and characterized to distinguish between zero strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

42
231
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 144 publications
(274 citation statements)
references
References 66 publications
42
231
1
Order By: Relevance
“…Again, since imposed strain-rates are zero in the = 90 o direction there is no variation of ̃9 0 and ̂9 0 at steadystate. Consistent with the observations of Faust et al (2011), the model predicts isotropic stress-fiber distributions when max = 0.1 but the distribution of becomes more anisotropic with increasing max with a clear alignment of stress-fibers perpendicular to the loading direction predicted in the max = 0.4 case. To understand this strain dependence at these very slow imposed cyclic frequencies, let us consider the max = 0.4 case corresponding to = 0.025 Hz, i.e.…”
Section: 2supporting
confidence: 79%
See 2 more Smart Citations
“…Again, since imposed strain-rates are zero in the = 90 o direction there is no variation of ̃9 0 and ̂9 0 at steadystate. Consistent with the observations of Faust et al (2011), the model predicts isotropic stress-fiber distributions when max = 0.1 but the distribution of becomes more anisotropic with increasing max with a clear alignment of stress-fibers perpendicular to the loading direction predicted in the max = 0.4 case. To understand this strain dependence at these very slow imposed cyclic frequencies, let us consider the max = 0.4 case corresponding to = 0.025 Hz, i.e.…”
Section: 2supporting
confidence: 79%
“…This hypothesis was further reinforced by the experiments of Tondon et al (2012) who demonstrated reduced sensitivity of cells subjected to fixed strain amplitudes but reduced frequencies of applied loading. However, this explanation contrasts with the observations of Faust et al (2011) who performed experiments with a fixed (low) value of applied strain-rate and varied the strain amplitude. The cells they investigated showed an increased strain avoidance when the imposed strain amplitude was increased beyond a critical value suggesting a sensitivity to strain amplitude rather than strain-rate.…”
Section: Introductioncontrasting
confidence: 70%
See 1 more Smart Citation
“…For instance, cells orient perpendicular to cyclic strain when cultured on stiff substrates or on biaxially constrained collagen gels (1)(2)(3)(4)(5)(6)(7). This phenomenon, called strain avoidance (SA), depends on the profile of the cyclic strain because the degree of cellular (re)orientation is proportional to the amplitude and frequency of the strain (1,2).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, cellular alignment generally corresponds to the main SF direction (2), and experiments have shown that these acto-myosin bundles are essential for the reorientation of cells in response to cyclic strain (3,5). On the other hand, FAs are crucial to sense and interact with topographical stimuli, because they form the link between cells and their surroundings (34).…”
Section: Introductionmentioning
confidence: 99%